From arid deserts to mesic meadows: divergent pathways regulating microbial respiration under grassland enclosure - Julihaiti, Asitaiken; Yiqiang, Dong; Shijie, Zhou; Tingting, Nie; Anjing, Jiang; Shazhou, An (Frontiers in Microbiology, 2025)
IntroductionAs a pivotal restoration strategy for alleviating grassland degradation, long-term enclosure practices effectively eliminate livestock disturbances while facilitating ecosystem self-recovery. Understanding the dynamics of soil microbial respiration under enclosure management is crucial, as it provides a scientific foundation for optimizing grassland utilization and contributes to global research on the terrestrial carbon cycle.MethodsWe conducted a comparative study across three distinct enclosed grassland ecosystems in Xinjiang, China: temperate desert, temperate steppe, and mountain meadow. Through analyzing microbial community structure, diversity, assembly processes, and respiration rates between 9-year enclosed and grazed areas, we identified key ecological shifts.ResultsThree key advancements emerged: (1) Enclosure implementation led to a marked improvement in soil resource availability, triggering microbial community shifts from oligotrophic to eutrophic states with substantial biodiversity increases (bacterial diversity: 2.2–14%; fungal diversity: 12.4–27.2%); (2) Divergent assembly mechanisms were observed where surface soil bacterial communities (0–5 cm depth) transitioned from 55.6 to 100% deterministic processes, directly contrasting with fungal communities that shifted from 11.1 to 55.6% stochastic dominance; (3) Partial Least Squares Path Modeling (PLS-PM) revealed distinct ecosystem-specific regulatory mechanisms underpinning reduced microbial respiration.DiscussionThe PLS-PM analysis detailed these distinct mechanisms: soil property-induced microbial metabolic trade-offs enhanced carbon use efficiency in temperate desert (R2 = 0.951), plant-mediated microbial assembly processes promoted efficient carbon cycling in temperate steppe (R2 = 0.455), and plant-driven suppression of microbial biomass dominated respiratory reduction in mountain meadow (R2 = 0.883). The research establishes that enclosure achieves carbon sequestration through divergent pathways across ecosystems, providing critical insights for optimizing grassland management strategies and enhancing climate change mitigation efforts.